(untitled) (Revista LIDER, 2020)
The establishment of a protected area installs new rules over the use and management of natural resources, modifying how people relate to their environment, as well as the way in which the space is comprehended and constructed. How does this process occur? How does the creation of protected natural areas transform or disrupt territories? The hypothesis that we present in this work is that the creation of protected areas, when it does not include local consensus and negotiation processes, may result in dynamics of deterritorialization, creating what Marc Augé (1993) referred to as non-places. From this perspective, we explain the meagre results both social and environmental of some natural protected areas in Mexico, and propose a vision of conservation focused in places, according to the anthropological connotation of the term.